Evaluating the Cyclic Behavior of the Sloped Extended End-plate Beam-to-column Connections - Miryahyavi, Mirreza; Khani, Reza; Hosseinzadeh, Yousef (Periodica Polytechnica Civil Engineering, 2023)
In the Northridge and Kobe earthquakes, brittle failure of the welded beam-to-column connections was observed in steel structures. So, bolted connections were considered as an alternative to these kinds of connections. Extended end-plate beam-to-column con-nection is one of the most commonly used connections in steel structure. In this article, the behavior of the sloped extended end-plate beam-to-column connections is studied. Finite element method was used to investigate the behavior of the connection by ABAQUS software. The main aim of the study was to investigate the cyclic behavior of the four beam-to-column connections with beam angles of 0, 10, 15, and 20 degrees with respect to horizon. Also, the behavior of the mentioned connections was compared with extended end-plate connections with perpendicular angle. Results showed that the ductility and moment-resisting capacity of the sloped extended end-plate beam-to-column connections decrease by increasing beam angle, but rotational and moment-resisting capacities of the models satisfy the limitation of the design codes such as 0.04 drift limit for bearing capacity before failure.